2007
DOI: 10.1080/00036840500447906
|View full text |Cite
|
Sign up to set email alerts
|

The effect of political regimes and technology on economic growth

Abstract: Do political regimes have a significant effect on economic growth? This study builds on the new neoclassical growth model to identify economic determinants of growth, and explicitly tests for the influence of political variables on economic performance for the 1990s. The results suggest that democracies and bureaucracies significantly outperform autocracies. Economic growth is also promoted by increased protection of property rights, and higher investment in education. Moreover, technology has become a require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…Literature proves that democracy supports economic growth (Barro 1996;Heo and Tan 2001;Barro and Sala-i-Martin 2004;Jamali et al 2007). Soysa et al (2010) and Boos and Holm-Müller (2013) show empirically that democratic structures also increase GS rates.…”
Section: The Political Systemmentioning
confidence: 95%
“…Literature proves that democracy supports economic growth (Barro 1996;Heo and Tan 2001;Barro and Sala-i-Martin 2004;Jamali et al 2007). Soysa et al (2010) and Boos and Holm-Müller (2013) show empirically that democratic structures also increase GS rates.…”
Section: The Political Systemmentioning
confidence: 95%
“…In their study of the effect of political regimes and technology on economic growth, Jamali et al (2007) find that democracies significantly outperform autocracies in this area, and so the type of government matters a great deal regarding economic growth. They also find that there are two other main determinants for economic growth: human capital and technology.…”
Section: It and Development: Theoretical Frameworkmentioning
confidence: 98%
“…Perhaps the most important of these factors is the level of human skills and capabilities required to make use of the new technologies. The most effective method for states to develop such capacities is through education (Jamali et al, 2007;Lee, 2001).…”
Section: It and Development: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent estimate for this type of computer is about $175 as per the Economic Times dated May 7, 2007. 11. In a recent panel-data-based study covering a sample of 58 countries for years 1990 through 1999, Jamali, Wandschneider, and Wunnava (2007) demonstrated that increased usage of technology (proxied by 00 computers per 000 individuals) has a significant impact on economic growth (i.e., annual percentage growth in real GDP per capita).…”
mentioning
confidence: 99%